Comparison of throttle devices to measure two-phase flowrates of wet gas with extremely-low liquid loading. (December 2020) - Li, Shanshan; Zheng, Xuebo; Zhao, Fan; He, Denghui; Bai, Bofeng
Abstract: The online measurement of wet gas with extremely-low liquid loading (Lockhart-Martinelli parameter lower than 0.02) remains a challenge. In this study, three types of throttle devices, Venturi, orifice plate and cone, are compared experimentally with air-water two-phase flow in a horizontal pipe of inner diameter of 50 mm. High-precision correlations are established to measure the gas and liquid flowrates via a single throttle device. Results show that the two-phase mass flow coefficient ( K ) of the three throttle devices all increase linearly with the liquid densiometric Froude number and the K correlations are established respectively to correct the gas mass flowrate deviation. The pressure loss ratio ( δ ) for Venturi is sensitive and monotonous to the liquid loading, which contributes to the high accuracy of liquid flowrate measurement. By incorporating the K correlations, both the gas and liquid mass flowrates can be predicted precisely. The relative error of the gas mass flowrate predicted by the Venturi is within ±2.0% at 95% confidence level, and that of the liquid mass flowrate is within ±15% at 90% confidence level. Highlights: Performance of three throttle devices for wet gas with extremely-low liquid loading are investigated. The two-phase flow coefficient and the pressure loss ratio are analyzed. The new gas and liquid mass flowrates measurement correlations are established. The Venturi shows high prediction accuracy on two phase flowrates measurement.